The Effect of Ration that Given Different Percentage Between Day and Night to Broiler Strain CP 707 Performance - Nova, K (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2008)
The present experiment was conducted to investigate (1) the effects of different percentage of ration between light and dark day to broiler performance, (2) the best level of percentage of ration that given during the light and dark day. This research was arrange with 5 treatments and 4 replications, each experimental units consist of 5 broilers. The treatmens were R1 (Ration that given 30% during light and 70% dark day); R2 (Ration that given 40% during light and 60% dark day); R3 (Ration that given 50% during light and 50% dark day); R4 (Ration that given 60% during light and 40% dark day); R5 (Ration that given 70% during light and 30% dark day). Ration were given 8x/day. The data were analyze by using Analysis of Variance in 0,05 or 0,01 significant degree. The result of this research showed that the different percentage of ration between light and dark day affected (P< 0,05) body weight gain and feed convertion, but not significant affected feed consumption. These result suggested that the ration which given 30% in light day and 70% in dark day is the best treatment influence body weight gain and feed convertion. (Animal Production 10(2): 118-121 (2008) Key Words: Broiler, performance, percentage of ration, light